Fermentasi Nira Nipah Skala Pilot Menjadi Bioetanol Menggunakan Saccharomyces Cerevisiae Dengan Penambahan Tween 80 Dan Ergosterol - Rafly Rafly; Chairul Chairul; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Ethanol consumption of the world for a variety of uses has increased very significantly in recent years. Therefore it is necessary to alternate sources of raw materials to manufacture bioethanol and bioethanol production can be increased. Nypa sap is one of potential materials to be processed into bioethanol. This research was conducted the pilot scale fermentation of nypa sap, using Tween 80 and ergosterol as suplement to obtain high concentration of bioethanol as well as prevent osmosis in cells. This work is aimed to study of bioethanol pilot scale production from nypa sap, to determine effect of fermentation time to bioethanol and to obtain maximum conditions on the process. And to determine effect of Tween 80 and ergosterol. Fermentation was conducted in 70 L fermentor having variations of fermentation time such as 24; 36; 48; 60; 72; 84 and 96 hours respectively, variations addition of Tween 80 of 250; 375; and 500 ml respectively, and ergosterol of 25; 37,5; and 50 gr. Stirring speed of 200 rpm and temperature of fermentation at room temperature (25 - 300C). Ethanol concentration was analyzed by using Gas Chromatography. Tween 80 and ergosterol effect on the activity of Saccharomyces cerevisiae in converting nypa sap into bioethanol. The process of fermentation maximum conditions indicated in the addition of Tween 80 [375 ml] and ergosterol [37,5 g] at the time of 84 hours having the initial sugar concentration of 258,641 mg/ml. Concentration bioethanol obtained in this condition at 16,602% (v/v) or 131.040 mg/ml.Keywords: Bioethanol, Ergosterol, Nypa sap, saccharomyces cerevisiae, Tween 80